Erratum to: Historical Highlight: The Chemical Characterization of the Pneumococcal Transforming Principle - Neil Greenspan (Case Western Reserve University, 2024)
Erratum to: The Chemical Characterization of the Pneumococcal Transforming Principle. doi: 10.20411/pai.v8i2.687 In the original publication, the title did not clearly distinguish this commentary from the originally published study. In this version, the title and the section header have been edited to more clearly denote this article as a commentary on the originally published study. --- The editors of Pathogens and Immunity are commemorating this month, the 80th anniversary of the publication of the landmark article by Oswald Avery, Colin MacLeod, and Maclyn McCarty in the Journal of Experimental Medicine on February 1, 1944 [1]. The study by Avery et al determined with extraordinary rigor the chemical nature of the so-called transforming principle inferred to exist by Frederick Griffith based on experiments he published in 1928